Rural tourism: support for destination competitiveness strategies from communitys’ perspective / Rozalina Abdul Razak - Abdul Razak, Rozalina (2010)
Nowadays, tourism industry becomes one of the profitable industries, which contribute to the growth of the country economy. Due to that factor, Malaysia can be considered as providential country by having unique tourism attractions that can be transformed into tourism production, which some of them are from rural tourism industry. Therefore, it is important to fully utilized rural tourism resources in order to create rural tourism product that have competitive edge. However, there are many factors need to be considered when embark in rural tourism sector. The most important thing to be considered is the support from the local community itself. This is because without the support and commitment from local community, all the planning and strategies cannot be succeeded. Therefore, the research proposes is to look at the support of destination competitiveness strategies among rural community in Perlis. Considering the community as the central to this process, they should be involved and affected by rural tourism. In order to do that, the entire development plan should benefit the community. A simple random sampling had been used which involves 182 respondents from rural community in Perlis. By using self reported questionnaires, survey had been done from one house to another by the researcher. The outcome of the research supports the hypotheses made and the findings also answered the research questions outlined in the proposed research. It is a great hope that the proposed research can be undertaken in order to benefit policy makers, educators, and tourism authorities, on the planning and developing destination competitiveness strategies by considering community’s perspective.